Exploring Challenges of Differentiated Instruction in English Foreign Language Classroom - Muhammad Surya Rifqi (LET: Linguistics, Literature and English Teaching Journal)
A qualitative case study is utilized in this study to explore the challenges faced while implementing differentiated instruction in the context of an English foreign language classroom. A purposive sample method was employed by selecting five participants who had engaged in differentiated instruction professional development and had experience implementing differentiated instruction. The study discovered that teachers faced challenges when organizing and delivering differentiated instruction, such as dealing with the selection of materials, methods, and assessments that match students' characteristics, teachers' intrinsic factors, a large number of students, time invested, and learning references. Participants offered suggestions to other teachers who want to use differentiated instruction by exploring more variations of learning activities, being open to technology, participating in various forms of professional development, recognizing the personalities of the students they teach, and spending more time preparing instruction so that student's learning needs are truly met.